Marketing mix in the gastronomic restoration establishments of the city of Riobamba - Haro Sosa, Giovanny; Naranjo Herrera, Juan; Naranjo Vaca, Myriam; Chávez García, Elsita (mktDESCUBRE, 2019)
Gastronomy is the art of preparing a good meal considering good manufacturing practices and the quality of products and service thus generating a gastronomic tourism; The food and beverage service seeks to meet the needs and expectations of the customer from the moment they enter the establishment until the moment they leave the establishment. The goal of this research is to know how 4P it has become a strategic plan by gastronomic companies to empower the self of a type of market, these attracting customers and creating the trust that allows consumer loyalty. In the design of the research, the analytical method has been used to allow and know the perspective of the entrepreneur and the client through the assessment regarding the research of marketing mix or 4P in the gastronomic establishments of the city of Riobamba that focuses on a general and middle class as their target market, with an innovative product based on technological advertising because the consumer today is very technological through social networks, being fundamental for the development of gastronomic companies.